Pengaruh Disiplin Belajar terhadap Hasil Belajar Siswa Sekolah Menengah Atas - Didit Darmawan; Ahmad Syauqi Albaar (CV. ALIM'SPUBLISHING, 2026)
This study focuses on the relationship between the regularity of study habits and pupils’ academic achievement at senior secondary school (SMA) level. The primary motivation for conducting this study is the phenomenon of declining study discipline among pupils. This is evident in habits such as procrastination, disorganised timetables, difficulties concentrating whilst the teacher is explaining, and breaches of school rules. To analyse this issue, the Systematic Literature Review (SLR) method with a qualitative descriptive approach was selected as the means of seeking answers. Data was collected through the examination of various written documents, such as scientific journals and research reports published over the last ten years (2015–2025). The findings indicate that discipline has a strong and decisive link to academic success. Students who demonstrate steadfastness in their studies are able to manage their time effectively, fulfil their school obligations regularly, and engage fully in classroom dynamics. This high level of responsibility leads to a comprehensive mastery of the subject matter and the attainment of optimal report card grades. Consequently, academic discipline is a key element in enhancing the performance of senior high school students and a driving force behind the smooth running of educational activities within the school.